(untitled) (Oshada, 2024)
Nurses are the workforce found in hospitals. Nurse satisfaction is influenced by performance. In addition to these factors, other factors that also affect performance are leadership, environment, motivation, discipline, compensation, organizational culture, satisfaction, and communication. The goal of this study is to determine the impact of job satisfaction on nurse performance in a hospital.. A thorough literature review was conducted for this investigation review approach is applied. The research’s data was taken from literature searches on the internet by utilizing the Portal Garuda and Google Scholar databases. The total number of articles received is 98. Next, the relevant article titles are identified and checked. A total of 26 articles were declared to meet the inclusion criteria. The abstract and the full article are then evaluated. Finally, 10 articles were included in the systematic literature review. The results showed that job satisfaction factors could affect nurses’ performance from 10 articles analyzed in the systematic literature review. This shows that a nurse’s satisfaction with her work will enhance nurses performance in improve the performance of nurses in completing their duties.